Public Participation in Community Planning Wangkrod Subdistrict Administrative Organization, Bangmunnak District, Phichit Province - Phureephong, Krit; Rojanaprapa, Weeranat; Salaenoy, Karnsith; Charoenyat, Supranee (Journal of Dhamma for Life, 2025)
This thesis conducts a quantitative research method to study the level of people’s participation in community planning in Wangkrod Subdistrict, Bangmunnak District, Phichit Province, classified by general status. The sample groups used in the study were people in Wangkrod Subdistrict, Bangmunnak District, Phichit Province, totaling 152 individuals. Data were collected using questionnaires, and the reliability of the questionnaire was obtained using Cronbach’s alpha coefficient. The statistics used in the data analysis included percentage, mean, standard deviation, and one-way ANOVA, with differences tested using the Scheffé method. This research found that public participation in the preparation of community plans in Wangkrod Subdistrict, Bangmunnak District, Phichit Province was overall at a moderate level. The aspect with the highest average was thinking and decision-making, which was at a high level. The item with the lowest mean was monitoring and evaluation, which was at a moderate level. In comparing people’s participation in community planning in Wangkrod Subdistrict, Bangmunnak District, Phichit Province, classified by gender, both overall and in each aspect, there was no difference. Classified by age, overall, there was no difference, but there was a statistically significant difference at the 0.05 level when classified by educational level. Overall, there was no difference, while in the monitoring and evaluation aspect, there was a statistically significant difference at the 0.05 level.